THE RELEVANCE OF FORMING THE IMAGE OF THE ARMED FORCES OF UKRAINE - Motyka, S. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The image of the Armed Forces of Ukraine is a complex and multifaceted socio-psychological and political phenomenon. A professionally created image functions as the most adequate informational object, creating public affection and recognition assuring the adequate perception of the Armed Forces as the power institution of the state. Thus, there's a relevant national challenge to form the positive image of the Armed Forces of Ukraine, and the numerous and versatile definitions of the term "image", the existence of a great number of approaches aimed at interpreting this definition, prove the multilateral aspects, the multidimensional categories and the significant scientific interest to this particular challenge.The Armed Forces of Ukraine is one of the most important elements of the political system of both state and society. In accordance with the Law of Ukraine "On the Armed Forces of Ukraine", the purpose of their existence is the protection of national interests, territorial integrity and inviolability of state borders. Considering the current state of development of the Ukrainian society, the state and its Armed Forces which is determined by the permanent increase of importance of the spiritual component, the issues of patriotic education and forming the image of the Armed Forces, are becoming the top state priority.The realities of modern life determine the objective necessity to develop a clear concept and the generic PR-strategy of the informativecommunication policy of the Armed Forces at a national level, with the aim to establish their positive image, based on the scientific approach and prominent world experience, yet taking into account the modern Ukrainian realities.The international experience has a variety of examples when the implementation of image technologies happens to play a significant role in solving a number of internal state developing tasks, namely: harmonizing the military-civil relations; increasing the level of the military-patriotic education and the general awareness of society in terms of task and activity of the Armed Forces, establishing firmness and sustainability of the moral-psychological state of the subordinated personnel, reinforcing military discipline etc.The information on the Armed Forces of Ukraine is to reflect the actual state of affairs. It is the irrelavance and the disproportion of the informational material about the Armed Forces of Ukraine and the realities of life that has promoted the lack of trust in the course of the years of Independence, not only to the military command in particular, but to the state authorities as a whole.The article presents an analysis of the relevance of forming the image of the Armed Forces of Ukraine.
Keywords: image, the Armed Forces of Ukraine, public opinion